Gairaigo derived from English in Japanese robotics terminology - Gama, Fitri Ifi (PAROLE: Journal of Linguistics and Education, 2024)
The objective of this research is to identify and classify Gairaigo derived from English in Japanese robotics terminology. The expected results of this study encompass deepening the comprehension of prospective entrants into the Japanese robotics sector and, more broadly, offering valuable insights to learners of the Japanese language on Gairaigo origination from English in Japanese robotics terminology. This study utilized a qualitative approach. The analysis of the gathered data involved the use of descriptive methods. The selected data was acquired from reputable websites of prominent robot developers from sources like Motoman and RoboticsBiz. The investigation identified 267 robotics terms written in English. After the data was verified by Japanese online dictionaries such as Tangorin and Jisho, this study identified 170 Gairaigo derived from English in Japanese robotics terminology. The result of the data analysis classified the Gairaigo derived from English in Japanese robotics terminology into three main categories: robot’s concepts, robot’s components, and robot’s movements.